Quality Management of Inpatient Medication Administration in Hong Kong Public Hospitals - Kiu Yan Kwong; Ben Y.F Fong (ACHSM, 2020)
Medicine maladministration can result in various side effects to patients, including serious complications, extended medical care, incapacity and death. In Hong Kong public hospitals, the pattern of medication error consists of prescribing error usually made by physicians, dispensing error resulted from pharmacists and dispensers, drug administration error caused by nurses and patient-care workers and technology-related error associated with technology used in the drug administration process. Medication Administration Record (MAR) and ward stock are the usual inpatient medication system within Hospital Authority public hospitals before the development of the electronic system, while the Inpatient Medication Order Entry (IPMOE) functions to provide real-time accessibility in patients' medication profiles by different professions and health units. However, several factors are related with medication errors. For instance, the ambiguous handwriting orders in the MAR prescribed by physicians affect the transcription by pharmacists and the administration procedures in ward by nurses. Administering medicines in ward stock before pharmacists vetting increase the chance of making errors. Poor interface issues between users and system, and the computer over-reliance are also contributed in resultant technology-related errors. In order to reduce the occurrence of medication incidents, implementation of Automated Pharmacy Distribution Systems  helps moving towards a closed loop medication management system. Modifying technologies in barcode assisted medication administration and enhancing the IPMOE with a pop-up message could help intercepting drug administration errors to patients.. The elimination of the potential risks arising from the prescribing, dispensing and drug administration processes brings the achievement of medication safety in Hong Kong public hospitals.